2021
DOI: 10.3892/etm.2021.9928
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA SNHG14 alleviates LPS-induced inflammation and apoptosis of PC12 cells by regulating miR-181b-5p

Abstract: Spinal cord injury (SCI) is a traumatic central nervous system disorder that leads to permanent functional loss, and unavailable treatment of this disease results in poor quality of life. However, the specific role of long non-coding RNA small nucleolar RNA host gene 14 (lncRNA SNHG14) in SCI has not been fully studied. The aim of the current study was to investigate the role of SNHG14 and its regulatory mechanism in lipopolysaccharide (LPS)-induced PC-12 cells. LPS was used to stimulate PC-12 cells to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Our validation of a direct regulation of XIAP expression by miR-199a-5p may have a functional impact on the triggered processes of the secondary damage after SCI such as apoptotic cell death. Our bioinformatic studies identified a total of six miRNAs candidates as regulators of XIAP, of which the down-regulated miR-340-5p and some miR-181 family members have been related to the treatment of SCI [62][63][64]. On the other hand, the upregulation of miR-21a-5p may have a protective effect on neurons after SCI by the regulation of PDCD4/caspase-3 pathway [55].…”
Section: Discussionmentioning
confidence: 96%
“…Our validation of a direct regulation of XIAP expression by miR-199a-5p may have a functional impact on the triggered processes of the secondary damage after SCI such as apoptotic cell death. Our bioinformatic studies identified a total of six miRNAs candidates as regulators of XIAP, of which the down-regulated miR-340-5p and some miR-181 family members have been related to the treatment of SCI [62][63][64]. On the other hand, the upregulation of miR-21a-5p may have a protective effect on neurons after SCI by the regulation of PDCD4/caspase-3 pathway [55].…”
Section: Discussionmentioning
confidence: 96%
“…LncRNA Vof-16 upregulates the expression of pro-inflammatory cytokines TNF-α and IL-6 by targeting rno-miR-346/rno-miR-205/rno-miR-874-3p and mediates inflammatory response during spinal cord injury [ 50 ]. Similarly, LncRNA SNHG14 plays a similar role in inflammatory injury in PC12 cells by binding to miR-181b-5p [ 51 ].…”
Section: Role Of Lncrnas In the Pathological Process Of Spinal Cord I...mentioning
confidence: 99%
“…It is a proven proto-oncogene in various cancers, including lung and cervical cancer. It is essential in activating inflammatory microglia, sepsis-induced acute kidney injury, and LPS-induced acute kidney injury ( Zhong et al, 2019 ; Jiang et al, 2021 ; Shi et al, 2021 ; Yang et al, 2021 ). Xie et al (2020) identified that SNHG14 regulates E-cadherin expression by interacting with EZH2, enhancing the progression of pancreatic ductal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%